1985
DOI: 10.1111/j.1476-5381.1985.tb08872.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of effects of a new dihydropyridine, Bay K 8644, and nifedipine on spontaneous mechanical activity in rat portal vein

Abstract: 1 In isolated portal veins from rats, Bay K 8644 (methyl-1, 4-dihydro-2, 6-dimethyl-3-nitro-4 (2-trifluoromethyl-phenyl) pyridine-5-carboxylate) increased the spontaneous mechanical activity in low but not in high concentrations. 2 The Bay K 8644-induced increase in spontaneous mechanical activity was abolished in Ca-free medium and restored by readdition of Ca. 3 Nifedipine abolished the augmenting effect of Bay K 8644 on the spontaneous mechanical activity; this effect of nifedipine could be eliminated by fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
0

Year Published

1987
1987
1994
1994

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 4 publications
5
11
0
Order By: Relevance
“…In the presence of 0.1 ,uM nifedipine, the spontaneous activity recovered and, moreover, enhanced by 0.1 AM Bay K 8644 to about 200% of the initial level (triangles). This confirmed the preceding observation shown by Mikkelsen (11). Even after Bay K 8644 was withdrawn together with nifedipine, the total contraction was maintained at a level higher than the control (see Fig.…”
Section: Resultssupporting
confidence: 79%
See 3 more Smart Citations
“…In the presence of 0.1 ,uM nifedipine, the spontaneous activity recovered and, moreover, enhanced by 0.1 AM Bay K 8644 to about 200% of the initial level (triangles). This confirmed the preceding observation shown by Mikkelsen (11). Even after Bay K 8644 was withdrawn together with nifedipine, the total contraction was maintained at a level higher than the control (see Fig.…”
Section: Resultssupporting
confidence: 79%
“…The present results support the preceding suggestion that the spontaneous activity of portal vein, as well as the high K+-induced contraction in aorta, is quite useful for assay ing a Ca antagonist (11,14). It is well established that each twitch contraction occurs as a consequence of a short burst of spontaneous action potentials (15,16), which are susceptible to Ca-antagonists (14).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…For example, in isolated heart preparations high doses of Bay K 8644 produced a negative inotropic effect (Schramm et al, 1983a;Franckowiak et al, 1985). Likewise, in isolated blood vessels Bay K 8644 exhibited a biphasic effect on the contractile force (Dube et al, 1985;Mikkelsen, 1985). Franckowiak et al (1985) have demonstrated that the (-)-enantiomer of Bay K 8644 possesses vasoconstrictor and positive inotropic effects whereas high concentrations of its antipode produce negative inotropic and vasodilator effects.…”
Section: Discussionmentioning
confidence: 99%